2006
DOI: 10.1093/aje/kwj267
|View full text |Cite
|
Sign up to set email alerts
|

Curry Consumption and Cognitive Function in the Elderly

Abstract: Curcumin, from the curry spice turmeric, has been shown to possess potent antioxidant and antiinflammatory properties and to reduce beta-amyloid and plaque burden in experimental studies, but epidemiologic evidence is lacking. The authors investigated the association between usual curry consumption level and cognitive function in elderly Asians. In a population-based cohort (n = 1,010) of nondemented elderly Asian subjects aged 60-93 years in 2003, the authors compared Mini-Mental State Examination (MMSE) scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
178
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(186 citation statements)
references
References 25 publications
2
178
1
5
Order By: Relevance
“…We note that the Phe-19 -Leu-34 contacts in A␤ 42 are thought to be intramolecular, whereas the salt bridge connecting Lys-28 and Asp-23 is thought to be between neighboring strands (35). Thus curcumin (like Zn 2ϩ ) seems to 4 B. Sahoo, unpublished data. preserve the gross intramolecular conformation, while disrupting the intermolecular arrangements.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…We note that the Phe-19 -Leu-34 contacts in A␤ 42 are thought to be intramolecular, whereas the salt bridge connecting Lys-28 and Asp-23 is thought to be between neighboring strands (35). Thus curcumin (like Zn 2ϩ ) seems to 4 B. Sahoo, unpublished data. preserve the gross intramolecular conformation, while disrupting the intermolecular arrangements.…”
Section: Resultsmentioning
confidence: 84%
“…Evidence for such a mode of action has indeed been seen for A␤ 40 -Zn 2ϩ (17,21) and also for A␤ 40 -Cur. 4 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent large, population-based study of 1010 elderly nondemented Asians, those who consumed curry ''occasionally'' and ''often or very often'' scored significantly better on the Mini-Mental State Examination (MMSE), a established measure of cognitive function, than did those who ''never or rarely'' consumed curry [190]. At the least, this finding warrants further investigation of curcumin's cognitive effects.…”
Section: 15mentioning
confidence: 97%
“…However, neurons induced in response to supra-physiological levels of caffeine have a lower survival rate than control cells and increased proliferation does not yield an increase in AHN [121]. Curcumin is a natural phenolic component of yellow curry spice that increases AHN in rodents [53] and epidemiological studies have reported better cognitive performance from curry Mouse Increased survival [62], [61], [54], [8] Omega 3 fatty acids Rat Increased (DHA) [46] Flavonoids Rat, chronically stressed Increased proliferation [3] Blueberry Rat Increased proliferation [12] Curcumin low concentrations Mouse Increased proliferation [53] Retinoic acid excess Mouse Decreased proliferation [16] Vitamin A deficiency Rat Decreased proliferation (rescued with retinoic acid) [9] Thiamine deficiency Mouse Decreased proliferation/survival [128] Zinc deficiency Rat male Decreased proliferation/survival [14] Folate consumption in ageing populations [83]. Moreover, in vitro studies have shown that curcumin exerted biphasic effects on progenitor cells; low concentrations stimulated cell proliferation, whereas high concentrations were cytotoxic.…”
Section: Dietary Modulation Of Adult Hippocampal Neurogenesismentioning
confidence: 99%